HUBUNGAN DUKUNGAN SUAMI DENGAN TINGKAT KECEMASAN PADA IBU BERSALIN - Selamita, Selamita; Afiyanti, Yati; Faridah, Ida (Nusantara Hasana Berdikari, 2022)
In Indonesia there are 373,000,000 pregnant women, while those who experience anxiety in facing childbirth are 107,000,000 people (28, 7%). Objective: To determine the relationship of husband's support to the level of anxiety in maternity mothers in Indonesia. Methods: The research design is descriptive correlation method using a cross sectional approach. Sampling using accidental sampling, there were 193 respondents from the total sampling results involving. The research instrument uses aÂ via Google form. Results: Most of the respondents domiciled in Banten province as many as 101 respondents (52.3%). The age of the respondents was in the age range of 20-35 years as many as 177 respondents (91.7%). The majority of respondents' education is Middle School (SMA or equivalent) as many as 96 respondents (49,6%) and on the job characteristics the majority of respondents work as many as 101 respondents (52.3%). Most of the respondents received good husband support as many as 114 respondents (59.1%) and most of the respondents had mild anxiety during childbirth as many as 76 respondents (39.4%). Results: Chi-square test and correlations test obtained p-value <0.0001 and R value 0,563, it can be concluded that Ho is rejected. With sufficient degree of strengethÂ Conclusion: which means that there is a significant relationship between husband's support and the level of anxiety in maternity mothers.